Exposed collagen in aged resin-dentin bonds produced on sound and caries-affected dentin in the presence of chlorhexidine - Sanabe, Mariane Emi [UNESP]; de Souza Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (Quintessence Publishing Co Inc, 2011)
Purpose: To evaluate the effect of chlorhexidine on the presence of collagen in aged resin-dentin bonds produced on sound and caries-affected dentin.Materials and Methods: Flat dentin surfaces were obtained from 16 sound molars, from which 8 were microbiologically processed for induction of caries. Single Bond 2 was applied to both sound and caries-affected substrates. In half of the teeth assigned for 6-month storage in water, the phosphoric acid demineralized dentin was impregnated with 2% chlorhexidine before the application of the adhesive. Specimens (2 x 2 x 5 mm) were produced and stored in water for 24 h, or 6 months in either water or mineral oil. The specimens were subjected to histological processing and sections were stained with Goldner's Trichrome. The thickness of the zone of exposed collagen was measured by optical microscopy and the data were subjected to two-way ANOVA and Tukey's test (alpha = 0.05).Results: There was no statistically significant difference (p > 0.05) between sound and caries-affected dentin regardless of the storage condition. For both substrates, significantly greater collagen exposure was observed after 6 months in water. Chlorhexidine-treated groups resulted in similar collagen exposure to that of the control and 6 months in water groups (p > 0.05), while no increase of the exposed collagen zone was observed after mineral oil storage.Conclusion: Aging in water resulted in degradation of the resin-dentin bond, as demonstrated by the increase of the zone of exposed collagen. However, the degradation of the exposed collagen was decelerated in the presence of chlorhexidine.
Keywords: dental caries; dentin; adhesive systems; collagen; chlorhexidine; longevity